Fluorescence Photoswitching in a Series of Metal‐Organic Frameworks Loaded with Different Anthracenes. Issue 29 (14th July 2021) - Tu, Min; Díaz Ramírez, Mariana Lizeth; Ibarra, Ilich A.; Hofkens, Johan; Ameloot, Rob
Abstract: The confinement of luminescent guest molecules in porous host materials can induce photophysical properties different from either component in isolation. In this work, we studied several host‐guest systems consisting of anthracene and its substituted analogs adsorbed in a series of metal‐organic frameworks (MOFs) and inorganic molecular sieves. Fluorescence photoswitching of the guest molecules through photoinduced dimerization is observed only in MOFs with a favorable pore volume and geometry. Abstract : Different anthracenes were encapsulated in a series of metal‐organic frameworks and inorganic molecular sieves. Fluorescence photoswitching (excimer emission to monomer emission) of the host‐guest systems through photoinduced dimerization is observed only in MOFs with a favorable pore volume and geometry.